The Prevalence of Undiagnosed Concussions in Athletes - Meehan, W. P.; Mannix, R. C.; O'Brien, M. J.; Collins, M. W. (Clinical Journal of Sport Medicine, 2013)
Objective: Previous studies suggest athletes underreport concussions. We sought to determine whether athletes in our clinics have sustained previous concussions that went undiagnosed.